2019
DOI: 10.1093/zoolinnean/zlz142
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the comb-tooth blenny genus Scartella (Blenniiformes: Blenniidae) reveals several cryptic lineages and a trans-Atlantic relationship

Abstract: Here we present the first phylogeny of the genus Scartella based on mitochondrial data. The analysis strongly corroborates the validity of all species of the genus and shows that Scartella cristata, a species with a disjunct distribution, is a lineage complex comprising five clades: two in Caribbean waters, another in the East Atlantic/Mediterranean and two in Brazil. Brazilian clades occur in sympatry from Rio de Janeiro to Rio Grande do Sul states (southern Brazil). One clade (BRA 1) is unique to Brazil, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…A more intriguing and complex biogeographical scenario is necessary to explain the diversification of Clepticus , Scartella, Scorpaena and Sphoeroides spengleri in the Atlantic. The phylogenetic analyses of Clepticus , Scartella and Sphoeroides spengleri revealed an unusual biogeographical relationship between the Brazilian Province and the Eastern Atlantic, with this pairs of species being sisters to the Caribbean region (Figures S13, S45 and S83; Beldade et al, 2009; Araujo et al, 2020). This indicates a separation between the Caribbean and South Atlantic lineages promoted by the Amazon‐Orinoco Barrier and subsequent isolation of populations off Brazil and the Eastern Atlantic (Araujo et al, 2020; Beldade et al, 2009; Floeter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A more intriguing and complex biogeographical scenario is necessary to explain the diversification of Clepticus , Scartella, Scorpaena and Sphoeroides spengleri in the Atlantic. The phylogenetic analyses of Clepticus , Scartella and Sphoeroides spengleri revealed an unusual biogeographical relationship between the Brazilian Province and the Eastern Atlantic, with this pairs of species being sisters to the Caribbean region (Figures S13, S45 and S83; Beldade et al, 2009; Araujo et al, 2020). This indicates a separation between the Caribbean and South Atlantic lineages promoted by the Amazon‐Orinoco Barrier and subsequent isolation of populations off Brazil and the Eastern Atlantic (Araujo et al, 2020; Beldade et al, 2009; Floeter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of all those situations, the recent wave of molecular systematic studies addressing CRFs in the Western Atlantic, including sequences from Brazil, revealed that several species considered widely distributed actually represent species complexes (e.g. Araujo et al, 2020; Dias et al, 2019; Maxfield et al, 2012; Muss et al, 2001; Smith‐Vaniz et al, 2018; Volk et al, 2021). This trend will likely be reinforced in future studies, also highlighting the need for more clear taxonomic recognition on the status of distinct populations in the Western Atlantic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Populations of Bathygobius soporator from the Gulf of Mexico and eastern U.S. have also been shown to be distinct from those in the Caribbean and Brazil (Tornabene et al 2010;Tornabene and Pezold 2011;Rodríguez-Rey et al 2017). Other examples of sister lineages occurring in the Caribbean versus the Gulf of Mexico/eastern U.S. can be found in the Menticirrus americanus species complex (Marceniuk et al 2020), the Lutjanus campechanus and L. purpureus species pair (Pedraza-Marrón et al 2019;da Silva et al 2020), the Scartella cristata species complex (Araujo et al 2020), the genus Bagre (Betancur-R 2009), and in Epinephelus adscensionis (Carlin et al 2003). In many cases these speciation patterns are thought to be a product of environmental variation between provinces as opposed to hard barriers to gene flow between the regions (Rocha et al 2005;Robertson and Cramer 2014).…”
Section: Discussionmentioning
confidence: 99%